VALUE-ADDED AND INCOME ANALYSIS OF FISH CRACKERS BUSINESS (CASE STUDY: SOUTH SIBOLGA SUB-DISTRICT, SIBOLGA CITY) - Lily Fauzia; Tiya Veronica; Mozart Bahauddin Darus; Mohammad Jufri (CV. Radja Publika, 2025)
This study aims to analyze the added value of fish cracker production and assess the feasibility of the business in South Sibolga Subdistrict, Sibolga City. The research location was selected purposively, involving two fish cracker producers as respondents, identified using a census method. The analysis utilized the Hayami value-added method and the Revenue-Cost (R/C) ratio to evaluate feasibility. Results show that the added value generated from fish cracker processing reached Rp 225,721.14 per kilogram, with a value-added ratio of 55.22%. The monthly income from the business amounted to Rp 5,573,076.35. The R/C ratio was 1.74, indicating that the fish cracker business is financially feasible. These findings highlight the potential of small-scale fish processing industries to enhance household income and promote local economic development.